The effect of the preparation method on the physical and chemical characteristics of propolis tinctures - Soós, Áron; Tóth, Nikoletta; Bódi, Éva; Várallyay, Szilvia; Molnár, Szabolcs; Kovács, Béla (Acta Agraria Debreceniensis, 2018)
The effect of the preparation method was examined with regards to the physical and chemical characteristics of the propolis tincture, namely the extraction time and the ethanol content of the extraction solvent to the dry matter, polyphenol, flavonoid, phosphorus, calcium and copper concentration, respectively. The dry matter, the polyphenol and the flavonoid content were the lowest in the water extract of the propolis; however, significant increase was noticed depending on the extraction time. Significantly higher concentrations were found in 50 V/V% tinctures. The highest dry matter and flavonoid contents were analysed in 100 V/V% tinctures, whereas highest polyphenol content was found in 80 V/V% tinctures. However, the differences were not significant in several cases between latter tinctures. Moreover, the increase was not determined in some cases depending on the extraction time. Phosphorus and calcium concentrations were decreased depending on the increasing ethanol content, whereas copper concentration was increased up to 80 V/V%. Higher increase was found in the case of 0 and 50 V/V% extracts than in 80 and 100 V/V% tinctures. Moreover, in latter cases, no significant differences were found on several occasions, depending on the extraction time. There was no connection between the flavonoids and the calcium as well as the phosphorus content, whereas flavonoids may be made complex with copper. However, the amount of the possible complex was negligible.